Tribal rehabilitation and its impacts on land use changes, food security and sustainable livelihoods: a case study in South India - Douglas Marowa; Pokkiyarath Manoj; Pozhamkandath Karthiayani Viswanathan; Sudheesh Manalil (Cogent Food & Agriculture)
Millions of tribals live in forests or adjacent protected areas and their food security and livelihoods depend on resources from the forests. Reportedly, about 40 to 60% of annual earnings of tribals, especially tribal women, is from collection and selling of forest produce. However, the idea of protecting biodiversity resulted in removal of people from forests and India was not an exception. This resulted in rehabilitation programmes as tribals were relocated to villages. The research sought to investigate the impacts of tribal rehabilitation on land use, food security and sustainable livelihoods in Rangayana Koppalu village in Karnataka, South India. In this paper, we developed a conceptual framework to determine the impacts of land use change on food security and livelihoods. To elicit information, 150 participants were selected through convenience sampling. We conducted PRA, besides in-depth interviews, survey interviews and focus group discussions to collect data. Results indicated food insecurity and unsustainable livelihoods with index scores of 10.03 and 0.27 respectively. The tribal rehabilitation programme had adverse impacts in the village. Policies on afforestation to consider undertaking a social cost benefit analysis of the rehabilitation process before implementation. Policies should provide for multi-stakeholder consultations before implementation of the tribal rehabilitation programmes.